Meeting the Challenges in Cancer Care Management During the SARS-Cov-2 Pandemic: A Retrospective Analysis. (5th October 2021) - Rasschaert, Marika; Vanclooster, Pieterjan; Depauw, Laura; Mertens, Tim; Roelant, Ella; Coenen, Elke; Anguille, Sebastien; Janssens, Annelies; Van Dam, Peter; Peeters, Marc
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has overwhelmed the capacity of healthcare systems worldwide. Cancer patients, in particular, are vulnerable and oncology departments drastically needed to modify their care systems and established new priorities. We evaluated the impact of SARS-CoV-2 on the activity of a single cancer center. Methods: We performed a retrospective analysis of (i) volumes of oncological activities (2020 vs 2019), (ii) patients' perception rate of the preventive measures, (iii) patients' SARS-CoV-2 infections, clinical signs thereof, and (iv) new diagnoses made during the SARS-CoV-2 pandemic. Results: As compared with a similar time frame in 2019, the overall activity in total numbers of outpatient chemotherapy administrations and specialist visits was not statistically different ( P = .961 and P = .252), while inpatient admissions decreased for both medical oncology and thoracic oncology (18% ( P = .0018) and 44% ( P < .0001), respectively). Cancer diagnosis plummeted (−34%), but no stage shift could be demonstrated. Acceptance and adoption of hygienic measures was high, as measured by a targeted questionnaire (>85%). However, only 46.2% of responding patients regarded telemedicine, although widely deployed, as an efficient surrogate to a consultation. Thirty-three patients developed SARS-CoV-2, 27 were hospitalized, and 11 died within this time frame. These infected patients were younger, current smokers, and suffered more comorbidities. Conclusions: This retrospective cohort analysis adds to the evidence that continuation of active cancer therapy and specialist visits is feasible and safe with the implementation of telemedicine. These data further confirm the impact of SARS-CoV-2 on cancer care management, cancer diagnosis, and impact of infection on cancer patients.